Power Line Communication Performance Channel Characteristics - Dipashree Navanath Duche; Vidya Gogate (Computer Engineering and Applications Journal, 2014)
Power lines form the medium of transmission in PLC systems. The original purpose of these lines is the transportation of electric signals at 50 or 60 Hz .This paper proposes a new channel modeling method for power line communications networks based on the multipath profile in the time domain. The new channel model is developed to be applied in a range of Power line Communications (PLC) research topics such as impulse noise modeling, deployment and coverage studies, and communications theory analysis. The statistical multipath parameters such as path arrival time, magnitude and interval for each category are analyzed to build the model. Each generated channel based on the proposed Power line communication that a performance channel characteristic represents a different realization of a PLC network